Importance of dam-free tributaries for conserving fish biodiversity in Neotropical reservoirs - Marques, Hugo [UNESP]; Dias, João Henrique Pinheiro [UNESP]; Perbiche-Neves, Gilmar; Kashiwaqui, Elaine Antoniassi Luiz; Ramos, Igor Paiva [UNESP] (Elsevier, 2018)
Dams change the hydrological dynamics, patterns of biological production and distribution of organisms in space and time. In contrast, tributary rivers can function as source areas in reservoirs, since they harbor spawning and early development grounds for native fish species. Here, we analyze a time series of the first 14 years after the impoundment of the Porto Primavera Reservoir, a large reservoir with free tributaries in southeastern Brazil. To evaluate the impact of damming on the fish assemblage, we evaluated the abundance (catch per unit effort, CPUE) and α (species richness and Shannon-Wiener index) and β (Sørensen dissimilarity and turnover) diversity of four sites distributed along the reservoir. Overall, there was no decreasing trend in the α diversity and no increasing trend in the β diversity relative to the initial year or among the sites over time. Despite the expected disturbance in the fish assemblage at the lacustrine site, the sites located near the tributary mouths presented resistant fish assemblages, compensating the results of the overall assessment. We attribute this unusual variation in the ecological attributes to source-sink demographic dynamics, with the undammed tributaries as the source and the reservoir as the sink for native species. We highlight that the presence of these rivers minimized the expected trend towards biotic homogenization, and the preservation of the tributaries is imperative since they contribute to diversity maintenance in areas that are already impacted by damming. The inclusion of this agenda in environmental management programs and new impoundment plans will allow a balance between the demand for electricity production and the conservation of fish diversity.
Keywords: Diversity; Fish fauna; Homogenization; Impoundments; Long-term monitoring; Tributaries